2019
DOI: 10.1002/term.2844
|View full text |Cite
|
Sign up to set email alerts
|

A promising therapeutic option for diabetic bladder dysfunction: Adipose tissue‐derived stem cells pretreated by defocused low‐energy shock wave

Abstract: Adipose tissue‐derived stem cells (ADSCs) have shown effectiveness in treating diabetic bladder dysfunction (DBD). In the present study, ADSCs pretreated by defocused low‐energy shock wave (DLSW) were first used to achieve better therapeutic effect. ADSCs were treated by DLSW prior to each passage. Secretions of vascular endothelial growth factor (VEGF) and nerve growth factor (NGF) were tested. Proliferation ability was examined by staining 5‐ethynyl‐2‐deoxyuridine (EdU) and assessing expressions of prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…9 The beneficial effects might be attributed to activated cell proliferation, 33 inhibition of inflammatory 34 and neovascularization. 35 Our findings also demonstrated that LESW could suppress cell apoptosis and increase cell proliferation and microvessel density to diminish renal tubular injury and accelerate renal recovery in rats subjected to IRI. What's more, LESW application did not induce significant damage in normal kidneys, which further validated the safety of LESW.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…9 The beneficial effects might be attributed to activated cell proliferation, 33 inhibition of inflammatory 34 and neovascularization. 35 Our findings also demonstrated that LESW could suppress cell apoptosis and increase cell proliferation and microvessel density to diminish renal tubular injury and accelerate renal recovery in rats subjected to IRI. What's more, LESW application did not induce significant damage in normal kidneys, which further validated the safety of LESW.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, growing evidence also suggests that administration of LESW can alleviate substantial damage and improve functional recovery in various of organs or tissues, such as the heart, 8 limb, 11 bladder 32 and penis 9 . The beneficial effects might be attributed to activated cell proliferation, 33 inhibition of inflammatory 34 and neovascularization 35 . Our findings also demonstrated that LESW could suppress cell apoptosis and increase cell proliferation and microvessel density to diminish renal tubular injury and accelerate renal recovery in rats subjected to IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Another study proved ADSCs pretreated by Li-EWST had potent therapeutic effect in diabetic bladder dysfunction by secreting VEGF and NGF to improve bladder innervation and revascularization. Compared with untreated ADSCs injection, injecting treated ADSCs also enhanced the migrations of endogenous stem cells to injured sites (P<0.05) (52). The roles of PEMF in regulating the osteogenic ability of human adipose-derived mesenchymal stromal cells (hADSC) have been also reported (53).…”
Section: Effect Of Mem On Adscsmentioning
confidence: 97%
“…This may be due mainly to its ability to activate cell proliferation and to inhibit inflammation and promote neovascularisation [72,73]. In addition, there were few reported side effects of LESWT application that caused significant damage to normal tissues, which further validates its safety [74]. Nevertheless, the efficacy of LESWT in the treatment of cavernous nerve injury erectile dysfunction needs to be further explored, including the effective energy frequency, pulse width, and pulse interval for nerve repair.…”
Section: Low-intensity Extracorporeal Shockwave Therapy (Leswt)mentioning
confidence: 99%